(untitled) (Research, Society and Development, 2022)
Several factors cause fluctuation of the vaginal flora and may favor alterations by pathogens such as Gardnerella vaginalis, Candida sp., Trichomonas vaginalis and Neisseria gonorrhoeae. Objective: To determine the prevalence of vaginal pathogens and risk factors associated with women in Marabá-PA, between February and March 2020. Sample and methods: Cross-sectional study with a sample of 150 women. Fangs were analyzed by fresh examination, bacterioscopy, fungus culture and germ tube testing. For statistical analysis, the G-Test and the Chisquare test were used, considering significant p <0.05. Results: The most prevalent vaginal pathogen was G. vaginalis (50.0%), followed by Candida sp. (35.6%), and N. gonorrhoeae (7.1%). Among the risk factors, diabetes presenting statistical significance p = 0.0062 for non-albicans Candida. Conclusion: In the municipality of Marabá, a high prevalence of vaginal pathogens was found. Among the risk factors influencing the appearance of vaginitis, it was found in this study, to correlate diabetes mellitus and vulvovaginal candidiasis. Early detection of cervical-vaginal diseases is very important, due to their clinical manifestations and probable complications resulting from them, as knowing this epidemiological profile can help management and health centers to develop targeted at this target audience.